2019
DOI: 10.1017/s1047951119002890
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of anomalous origin of one pulmonary artery branch by two-dimensional echocardiography: summary of 12 cases

Abstract: Objectives:To improve the prenatal diagnosis for anomalous origin of pulmonary artery branches by comparing and analyzing different types of fetal echocardiography features.Methods:Between June 2012 and December 2018, fetal echocardiographic features were analyzed retrospectively from fetuses with a prenatal diagnosis of anomalous origin of pulmonary artery branch. The main points of identification were summarized.Results:A total of 12 fetuses were diagnosed, including anomalous origin of a pulmonary artery br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In the cases of UAPA, the color blood flow signal of the pulmonary artery branch could be seen in the parenchyma of the affected side; A three‐vessel trachea view and a coronary view of the initial part of the innominate artery showed that the affected pulmonary artery was connected to the innominate artery by the ipsilateral arterial duct; The distal LPA connected with the ventral arch of the aorta (combining TOF); The absence of the left proximal pulmonary artery combined with the right arch and the absence of the right proximal pulmonary artery combined with the left arch. In the cases of AOPA, three‐vessel and trachea view (3VT view) and long axial views of the left ventricular outflow tract showed the affected pulmonary artery emanating from the left or right posterior wall of the ascending aorta (near aortic valve level) 2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the cases of UAPA, the color blood flow signal of the pulmonary artery branch could be seen in the parenchyma of the affected side; A three‐vessel trachea view and a coronary view of the initial part of the innominate artery showed that the affected pulmonary artery was connected to the innominate artery by the ipsilateral arterial duct; The distal LPA connected with the ventral arch of the aorta (combining TOF); The absence of the left proximal pulmonary artery combined with the right arch and the absence of the right proximal pulmonary artery combined with the left arch. In the cases of AOPA, three‐vessel and trachea view (3VT view) and long axial views of the left ventricular outflow tract showed the affected pulmonary artery emanating from the left or right posterior wall of the ascending aorta (near aortic valve level) 2 …”
Section: Discussionmentioning
confidence: 99%
“…1 AOPA can be divided into proximal and distal types according to the distance between the origin of the pulmonary artery and the aortic valve. 2 The most common pulmonary origin abnormality is one of the pulmonary arteries (right or left) arising from the ascending aorta. 3 Here we presented an extremely rare case of anomalous origin of the right pulmonary artery from the descending aorta (DAo) in a fetus at 24 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LPAS is a type of anomalous origin of the pulmonary artery, which should be distinguished from the absence of LPA, and LPA anomaly originates from the aorta. The absence of the LPA refers to the proximal interruption of LPA, with the distal pulmonary artery being usually intact in the lungs [7]. LPA anomaly originating from the aorta is also an extremely rare malformation, with a normal origin of the RPA from the main pulmonary artery [6].…”
Section: Discussionmentioning
confidence: 99%
“…It refers to the proximal interruption of right pulmonary artery , with the distal section arising from the base of the brachiocephalic artery (BA) via the ipsilateral ductus arteriosus (DA). There have been sporadic reports of antenatal diagnoses using two‐dimensional (2D) ultrasound 1,2 . However, to the best of our knowledge, this is the first case applying spatiotemporal image correlation, combined with high definition (STIC‐HD) live flow rendering mode for prenatal diagnosis of DODRPA with BDA.…”
Section: Figurementioning
confidence: 97%